Istikhdāmu al Kitābi “al Ta’līmi al Sarī’i ‘alā Kafā’ati al Ṭullābi li Fahmi Qawā’idi al Lughati al Arabiyyati bi al Madrasati al ‘Āliyati al Hukūmiyyati bi Jāmbī. - Prihartini, Yogia; Hasnah, Nur (Al-Uslub: Journal of Arabic Linguistic and Literature, 2021)
Teaching the Arabic language is an educational process that promotes the efficiency of language skills, both verbally and in writing, and as it contains the basic skills of listening, speaking, reading, writing, and translation. Access to these skills requires educational potential factors, one of which is textbooks. The book was a basic source of science and knowledge. A good book is a book that is easy to understand and teach, and it carries to the desired education goal. What is meant by the book in this research is the book “Quick Teaching of the Arabic Language. Focusing the research on the students and the book they used to guide their competency in language skills in the book “Quick Teaching on Arabic Grammar” and their level of success with this book. This research benefited from the field method, where the writer looked directly at the site of the research and gave the interview, compilation, and documentation then analyzed the data received through induction, deduction, and comparison. The result of the research is that the book " Quick Teaching on Arabic Grammar" is easy to understand in use and includes explanations in the Indonesian language and its materials starting from the organized foundation that is to be developed in the Arabic language. However, the students are still declining in understanding the Arabic language, and their proficiency in language skills is still light until the goal of teaching a good Arabic language has not been reached.